Stefan Javors'kyj's Panegyrics : 1684-1691 - Awianowicz, Bartosz B.,; Niedźwiedź, Jakub, (Literature and Cultural Studies E-Books Online, Collection 2026, 2025)
This book presents the first edition of Polish and Latin works by Stefan Javors'kyj (1658-1722), the leading author of Ukrainian literature of his time. The book contains four panegyrics dedicated to the Ukrainian political and ecclesiastical leaders, Hetman Ivan Mazepa and Metropolitan Barlaam Jasyns'kyj. In his masterful books, Javors'kyj combines emblems, lyric and epic poetry with prose in two languages. The edition will help to bring Ukrainian texts into the canon of early modern European literature and to recover an important fragment of literary history. Edited by Jakub Niedźwiedź and Bartosz B. Awianowicz with an introduction by Jakub Niedźwiedź